Dampak Pemenuhan Kebutuhan Dasar Karyawan Terhadap Kualitas Kerja Pegawai Rumah Sakit - Bima, Nur; Iskandar, Iskandar (Eko dan Bisnis: Riau Economic and Business Review, 2024)
This research was conducted at Eka Hospital Pekanbaru, which is located at Jalan Soekarno Hatta Km. 6.5 – Pekanbaru, Riau Indonesia, Postal code 28292. The purpose of this study was to determine the effect of motivation on employee performance at Eka Hospital Pekanbaru. In addition, this study aims to complete the requirements for completing lectures at the Riau Economics College (STIE-Riau). To achieve this goal, a research was conducted using a sample of 59 people, using a simple random sampling method (accidental random sampling). The data analysis method used simple linear regression. Based on the test results, the t-count is greater than the t-table (10,662 > 2.002). It can be concluded that the motivation variable has a positive and significant effect on employee performance at Eka Hospital Pekanbaru. The value of R. Square (R2) of 0.666 (66.6%) explains that the motivation variable contributes to the influence of employee performance at Eka Hospital Pekanbaru by 66.6%. While the remaining 33.4% describes other independent variables that were not observed in this study. Recommendations that can be submitted It is expected that the company pays attention to the employees of Eka Hospital Hospital in order to get an annual bonus from the company because this gets the lowest response from respondents.